Human dignity : the constitutional value and the constitutional right - Barak, Aharon (Cambridge, United Kingdom : Cambridge University Press, 2015)
'The concept of human dignity has a 2500 year history. As it moved through history, the concept was been influenced by different religions which held it as an important component of their theological approach. It was also influenced by the views of philosophers who developed human dignity in their contemplations. In the 20th century, the concept encountered a new phenomenon. The atrocities of the Second World War, and particularly the Holocaust of the Jewish people, brought human dignity into the forefront of legal discourse. As a result, constitutional and international legal texts began to adopt the concept, and jurists appeared alongside the theologians and the philosophers. Legal scholars were called upon to determine the theoretical basis of human dignity as a constitutional value and as a constitutional right. Judges were required to solve practical problems created by the constitutionalization of human dignity, as a value or as a right'--
The various aspects of human dignity -- The intellectual history of the social value of human dignity -- Human dignity as a value and as a right in international documents -- Human dignity as a value and as a right in constitutions -- Purposive constitutional interpretation -- The role of human dignity as a constitutional value -- Three types of model for determining the content of the constitutional value of human dignity -- Recognition of the constitutional right to human dignity and its content -- Human dignity as a framework right (mother-right) -- The area covered by the right to human dignity -- Human dignity in American constitutional law -- Human dignity in Canadian constitutional law -- Human dignity in German constitutional law -- Human dignity in South African constitutional law -- Human dignity in Israeli constitutional law.
Includes bibliographical references (pages 308-346) and index.
Keywords: Respect for persons -- Law and legislation -- Israel; Human rights -- Israel; Respect for persons -- Law and legislation; Human rights